Local Electric Field Promoted Kinetics and Interfacial Stability of a Phosphorus Anode with Ionic Covalent Organic Frameworks. Issue 3 (16th December 2022) - Cao, Yu; Zhang, Shaojie; Zhang, Baoshan; Han, Chengyu; Zhang, Yiming; Wang, Xiaoyi; Liu, Shuo; Gong, Haochen; Liu, Xinyi; Fang, Siyu; Pan, Fusheng; Sun, Jie
Abstract: A phosphorus anode is a promising option for energy‐storage applications because of its high theoretical specific capacity and safe lithiation potential. However, the multiphase phosphorus lithiation/delithiation reactions and soluble reaction intermediates cause sluggish reaction kinetics and loss of active materials. Herein, a novel local electric field (LEF) strategy is proposed to inhibit the intermediates dissolution and promote the reaction kinetics by optimizing ionic covalent organic frameworks (iCOFs). Among them, the LEF induced by the cationic covalent organic framework effectively enhances the electrochemical performance of the phosphorus anode. The strong electrostatic interaction between the polyphosphides and cationic covalent organic framework confines the dissolution of active materials and tailors the electronic structure of polyphosphides to accelerate the reaction kinetics. The cationic covalent‐organic‐framework‐assisted phosphorus anode provides a high capacity of 1227.8 mAh g −1 at 10.4 A g −1 (8.6 C) and a high‐capacity retention of 87% after 500 cycles at 1.3 A g −1 . This work not only broadens the application of iCOFs for phosphorus anode but also inspires the great potential of the local electric field in battery technology. Abstract : The cationic covalent organic framework creates a local electric field to regulate the reaction process of phosphorus anode. The local electric field can confine the soluble intermediate lithium polyphosphide species, change the electronic structure of polyphosphide anions to accelerate the reaction kinetics, and induce the generation of stable and tough SEI for long cycling stability.